Comparison between patient control analgesia combine with periarticular drug injection and patient control analgesia alone in total knee arthroplasty - Mohd Fikri bin Saari (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
This study intended to evaluate the efficacy of periarticular drug cocktail injection in managing postoperative pain in total knee arthroplasty in terms of pain and morphine consumptions. Patients who were diagnosed as primary osteoarthritis of the knee who underwent total knee replacement were enrolled in this study. Intervention group received cocktail injection of bupivacaine, adrenaline, morphine sulphate and diclofenac sodium at periarticular region during the operation. Both groups were started on PCA morphine post-operatively. Pain score at 6, 12 and 24 hour post-operative period recorded and total morphine consumption were recorded. There were 54 patients recruited with 27 of subjects in each arm. The mean age of the patient was 63.59 years old. There were 34 female and 20 male subjects. Chinese were the majority of the patient with 50% followed by Malay 40.7% and Indian 9.3%. The mean visual analog score in intervention group at 6 hour post operative period was statistically significant compared to control group. The mean visual analog score at 12 hours period was lower in intervention group but was not significant. There was no difference in visual analog score in both groups at 24 hours post operation. Total morphine consumption at the first 24 hour period post operation was lower in the intervention group and is statistically significant. Periarticular injection of bupivacaine, adrenaline, morphine sulphate and diclofenac sodium at periarticular region during total knee arthroplasty is effective to reduce post-operative pain and to reduce total morphine consumption in early post-operative period.